Implementation Of Rehabilitation In Judges’ Decisions Toward Juvenile Offenders Who Abuse Category I Narcotics For Personal Use: (Case Study Of Decision No. 1/Pid-Sus Anak/Pn Sgr) - Widiastuti, Kadek Ayu Sri; Yuliartini, Ni Putu Rai; Mangku, Dewa Gede Sudika (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This study aims to (1) analyze the legal considerations of the panel of judges in imposing a sentence of imprisonment without an order for rehabilitation on a child who abused Category I narcotics for personal use in Decision Number 1/Pid.Sus-Anak/2019/PN Sgr, and (2) examine the legal consequences of the absence of a rehabilitation order in the operative part of the judgment concerning the implementation of rehabilitation for a child who abused Category I narcotics for personal use. The research method employed is empirical legal research with a descriptive nature. The study was conducted at the Singaraja District Court and the National Narcotics Agency of Buleleng Regency. Data collection techniques included interviews, observation, and document study, with subjects determined through purposive sampling. The data processing and analysis were carried out qualitatively. The results of the study indicate that (1) the panel of judges in Decision Number 1/Pid.Sus-Anak/2019/PN Sgr declared the child legally and convincingly guilty of violating Article 127 paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics and imposed a sentence of six (6) months’ imprisonment without ordering medical or social rehabilitation. In fact, based on the facts revealed during trial and the criteria set forth in Supreme Court Circular Letter (SEMA) Number 4 of 2010, the child met the requirements to be classified as an addict who is legally entitled to mandatory rehabilitation. Therefore, the consideration was deemed inconsistent with Article 54 of the Narcotics Law and the principle of the best interests of the child under the Juvenile Criminal Justice System Law. (2) The omission of a rehabilitation order in the operative part of the judgment creates a legal vacuum for the National Narcotics Agency in executing rehabilitation measures, resulting in the child serving imprisonment without receiving medical and social recovery, potentially increasing the risk of recidivism and hindering the achievement of the educational and restorative objectives of juvenile sentencing.